The Macroeconomic Consequences of Wage Indexation Revisited - Jadresic, Esteban (IMF Working Papers; Working Paper, 1998)
Since the mid-1970s, there has been considerable research on the macroeconomic consequences of wage indexation. Nonetheless, until recently, this research had not explicitly explored the implications of contracts that index wages to lagged inflation, the usual type of wage indexation observed in practice. Drawing mainly on recent research by the author, this paper examines the consequences of wage indexation to lagged inflation on aggregate wage formation, the cost of disinflation under money- and exchange-rate-based stabilization, the variability of output under alternative shocks and policy regimes, the choice of exchange rate regime, and the level and variability of inflation.